(untitled) (Damascus University Journal for engineering sciences, 2022)
Abstract expressionism is one of the most important contemporary plastic currents that prevailed in post-World War II art, whose methods, representations and motives have branched into a Rank of complexity and pluralism that has at times confused art critics. Antonio Tapis is one of the most important representatives of this current in Spain through his observations and works of art. This research aims to delve deeper into Tapis’s abstract expressive vision by focusing on the concepts of "empathy and abstraction" presented by the researcher and art critic) Worringer ( at the beginning of the 20th century, and his views had a direct impact on artists who tended to express abstract expression in art, with the aim of reaching a critical vision to taste Tapis’ printmaking abstract expressionist experience.